Rancang Bangun Digital Library Berbasis Mobile (Studi Kasus : Universitas Muhammadiyah Purworejo) - Hamid Muhammad Jumasa (INTEK : Jurnal Informatika dan Teknologi Informasi, 2019)
The development of information technology has currently been growing rapidly and provided many benefits in various fields, one of which is the library. The application of information tech-nology to the library is usually called a digital library (digital library). Digital library makes it easy for users to obtain information sources easily. Users can quickly search for book data in-formation, find out the number of books available, makes direct borrowing etc. Libraries in a university support the implementation of education, and teaching, research and community ser-vice. The library in the university has a collection of reference books and research reports that are always obtained every year.The presence of smartphone technology makes it easier for users to be comfortable, fast and easy in completing their work. However, there are difficulties which have to deal with while the display interface of a web-based information system does not support to be displayed on smartphone screen. This has an impact on the difficulties encountered by users in accessing the information. Currently, the digital libraries at Muhammadiyah University of Purworejo are web-based. But it has obstacles with display interface which does not support to be displayed in mobile version. Besides that there are menus that are still not categorized correctly. In order to improve access and give users easiness, this research made the design of a mobile-based Digital Library.